ANALISIS PENGGUNAAN INERT GAS SYSTEM PADA PROSES BONGKAR GASOLINE RON 92 DI MT. SC ESTEEM LII - Sarli Armada Divia; Bayu Yudho Baskoro; Rizal Rochmansyah; M. Kurniawan; Meilinasari (STKIP Subang, 2026)
Sarli Armada Divia, 2026 “Analysis of the Use of the Inert Gas System in the Discharge Process of Gasoline RON 92 on MT. SC ESTEEM LII.” Supervised by Mr. Bayu Yudho Baskoro, S.S.T.Pel., M.Tr.T and Mr. M. Kurniawan, M.Pd.I. His study aims to analyze the use of the Inert Gas System (IGS) in improving work safety and preventing fire and explosion risks during the discharge of Gasoline RON 92 on MT. SC ESTEEM LII. Gasoline is a highly volatile and flammable cargo that can form explosive mixtures when combined with oxygen, making INERT GAS SYSTEM (IGS) essential to reduce oxygen levels and maintain positive tank pressure. This research applies a descriptive qualitative method through direct observation, crew interviews, and documentation, with analysis based on ISGOTT standards. The results show that the INERT GAS SYSTEM (IGS) is effective in reducing oxygen levels and preventing air ingress into the tanks. However, its effectiveness is influenced by human factors and equipment conditions. Therefore, routine maintenance, continuous training, and optimal supervision are necessary to ensure safe ship operations.